Grief, Caregiving Burden, and the Pandemic: Triggers of Depression in Middle-Aged Women (Case Report) - Rizka Aulia Rahma; Era Catur Prasetya (Universitas Muhammadiyah Surabaya, 2026)
Introduction: Losing the loved one is an emotional experience that can trigger mental health disorders such as depression, post-traumatic stress disorder, and prolonged grief disorder. When the grieving process is exacerbated by economic pressure and social isolation during the COVID-19 pandemic, the risk of psychiatric disorders increases significantly, especially in middle-aged women who are the primary caregivers in their families. Content: The diagnosis of a moderate depressive episode is confirmed in a 58-year-old female patient who presented to the psychiatric clinic with complaints of difficulty sleeping, prolonged sadness, decreased appetite, and excessive fear of death. This case highlights the complex interaction between grief, caregiving burden, and the pandemic crisis as triggers for depression. Literature studies show that elderly caregivers with dementia during the pandemic have a high risk of depression, especially middle-aged women. Conclusion: This case underscores the importance of a biopsychosocial approach and multidisciplinary interventions in managing depression triggered by grief and caregiving burden, especially in the context of a pandemic.